OPTIMIZATION OF INTERPERSONAL COMMUNICATION AND WORK ENVIRONMENT FOR CAREER DEVELOPMENT AT PT. BALI REGIONAL DEVELOPMENT BANK, BADUNG BRANCH - Wijaya, Gede Crisna; Trisnandini, Putu Vidya (LPPM Univ. Ibn Khaldun Bogor, 2023)
In the current era of globalization, in a company career development is very important because doing career development can make a company more advanced and make the abilities of company employees increase and develop in doing a job. The career development process is influenced by several factors, including interpersonal communication and the work environment. Based on observations made at PT. Regional Development Bank Bali Badung Branch there are problems with career development that are influenced by interpersonal communication and the work environment. It is not uncommon to find problems related to communication within the company, both communication between superiors and subordinates, as well as co-workers. In addition, there are problems in the current working environment that are still not comfortable for employees, resulting in less than optimal performance in their duties. The existence of effective communication will facilitate employee activities at work and minimize the occurrence of miscommunication as well as a conducive work environment can increase employee performance optimally and on the contrary further enhance employee career development. Therefore, interpersonal communication and work environment are needed to support career development at PT. Regional Development Bank of Bali Badung Branch.